EXPERT ACTIVITIES IN HIGHER EDUCATION SPHERE: THE COMPETENCE DIMENSION - Нalyna Kalinicheva (Borys Grinchenko Kyiv Metropolitan University, 2022)
In the context of building state-public administration of higher education, when the state, society and the individual are equal subjects of the educational process, the problem of carrying out expert activities in higher education institutions by specialists who have the necessary level of knowledge, skills and general and special competencies. The purpose of the article is to study the competencies of experts in the field of higher education aimed at ensuring its quality. The author emphasizes the theoretical and practical aspects of the implementation of expert activities in the field of higher education and the requirements for the competencies of educational experts in higher education institutions. Competence is defined by the author as an integral characteristic of a person, which reflects his ability on the basis of a dynamic combination of knowledge, skills, personal traits and qualities, to conduct professional, educational and other activities that contribute to its development. Expertise in the field of higher education is considered in the article as a method of analysis and cognitive process aimed at finding out the cause-and-effect relationships. Educational expertise acts as a special mechanism for managing university education, when equal partners and participants in the educational process are jointly responsible for the quality of higher education, its monitoring and operation. Accordingly, expert activity in the field of higher education performs educational, methodological, consulting, recommendation, forecasting and innovation functions. It is emphasized that the implementation of expert activities in the higher education system requires from experts a wide range of general and professional competencies and soft skills for impartial assessment of the educational environment, quality of educational programs, management decisions and more. Educational analytics and consulting activities are aimed at directing the administration of higher education institutions and participants in the educational process to make optimal strategic decisions aimed at ensuring the quality of higher education.